A case report of hereditary leiomyomatosis and renal cell carcinoma (HLRCC) - Sunao Nohara; Shotaro Nakanishi; Tomoki Matsuo; Tomoko Tamaki; Seiici Saito (Urology Case Reports, 2024)
Leiomyomatosis and renal cell carcinoma (HLRCC) are rare autosomal dominant cancer syndromes characterized by cutaneous leiomyoma, uterine leiomyoma, and renal cell carcinoma (RCC). RCC in HLRCC is an aggressive metastatic tumor that develops at a young age. Here, we report the case of a patient with HLRCC who was diagnosed after the spontaneous rupture of a renal tumor. The patient underwent cytoreductive surgery, followed by combination therapy with the immune checkpoint inhibitor (ICI) nivolumab and cabozantinib, a tyrosine kinase inhibitor (TKI); however, no improvements were achieved.